Study the effect of smoking, sex and age factor in the speed of blood clots - Leila Jassem Shaabth (Al-Qadisiyah Journal of Pure Science, 2018)
The study Conducted, for the purpose of verification of the effect of smoking, sex and age groups, the blood to clot, and the study was conducted in the cardiology center in the city of Nasiriyah for the period from January 2 to March 1 of the year 2016. The study included taking (100) blood sample from the auditors of the Center for Patients heart disease in the city of Nasiriyah was taking information from patients according to information prepared by researchers form.Results of the study showed that the overall infection rate of the total sample is 64 % (64 references) rapidly infected blood clotting, and the percentage of reviewers is rapidly infected blood clotting is 36 % (36 references). And results of the study showed the effect of some factors on the speed of blood clotting, and most important of these factors are smoking worker as she was quickly blood clotting smokers with ratio is 59.38 % (38 references), while non-smokers with blood clotting were quickly accounted for 40.62% ie (26 references).As well as the results of the study showed the effect of sex workers in the incidence of blood clotting quickly as was the proportion of infected males speeds blood clotting is higher than the proportion of females amounted to 62.5% (40 references) while she was quickly blood clotting female-positive rate of 37.5 % (24 review ). The results also showed a lack of effect of the age factor in the speed of blood clotting, with two age groups were taken first category is less than 40 years and the second category is the largest of the 40 years they were the proportion of people in the second category 56.25% (36 references) or age group first it was infected with the proportion of 43.75 % (28 references). And 34.38 % (22 references) of the injured fast blood clotting have been subjected beforehand to a bloody and 65.62 % (42 strokes references) have not been exposed to blood clot in advance. It results above show that the blood clotting speed is affected by a factor of smoking and worker sex (where it was found that the percentage of male cases higher than females almost twice), and did not factor of aging with a clear impact on the incidence of speeds blood clotting, and the results also showed that people quickly blood clots are more likely to develop blood clots.